Evaluation and Strategy: Strengthening Indonesia Council of Representatives of the Regions - Melati, Dwi Putri; Rosida, Nikmah; Siswanto, Heni (International Journal of Criminology and Sociology, 2021)
The Council of Representatives of the Regions emerged through the 1945 Constitution third amendment. The Council of Representatives of the Regions intended to represent regional interests and regional society in the central legislation making processes and products, to perform checks and balances principle on The People’s Representative Council which is a political representation that brings and struggles the aspirations and interests of political parties at the central level. The Council of Representatives of the Regions also acts as a guardian of decentralization and regional autonomy. The most fundamental problem for The Council of Representatives of the Regions is its institutional weaknesses. In legislation weaknesses terms, budgeting, and supervision have affected The Council of Representatives of the Regions in maximizing its performances. The Law regarding Indonesia Legislative Branch does not mandate legislation as The Council of Representatives of the Regions tasks. This provision can not be used as a guideline to describe the scope of duties, which are the limits of their authority in The Council of Representatives of the Regions order. On the other hand, after the Constitutional Court Decision Number 92/PUU-X/2012 and Number 79/PUU-XII/2014 issued, the relations that were later present were the three-party discussion model of The People’s Representative Council-The Council of Representatives of the Regions-President (Tripartite). Based on those facts, this article focuses on the evaluation of 15 years of The Council of Representatives of the Regions establishment and strategy to strengthen it.